Developing the Local Wisdom-Based Pop-Up Book for Fifth-Grade Students - Budiyanto, Satrio; Laila, Fatmawati (International Journal of Learning Reformation in Elementary Education, 2024)
Within the context of Kurikulum Merdeka (Indonesian Curriculum), traditional teaching methods often fail to engage elementary students effectively, leading to boredom and limited learning experiences. To address this, a study was conducted at a public primary school in Wonosobo Regency, revealing the need for interactive learning materials. This research focuses on developing Local Wisdom-based Pop-Up Books tailored for fifth-grade students in Indonesia. Through rigorous evaluation by experts and positive feedback from teachers and students, the Pop-Up Books prove to be highly effective in enhancing learning outcomes. Statistical analysis confirms significant improvements in student performance after using the Pop-Up Books. This study highlights the importance of innovative learning media in enriching educational experiences for elementary students.